Una urna puede ser el mejor preservativo - Germán Labrador Méndez (Mélanges de la Casa de Velázquez, 2020)
The poetics of democracy—understood as a regime of representation, an articulation of the symbolic and the affective, or as a visual, performative or linguistic order that serves to codify a certain experience of time—requires the representation of the government of the bodies through the representation of the autonomy of their passions. From this premise, this text questions the connections between the public and the private, the political and the erotic in the context of the Spanish transition and, more specifically, of the celebration of the first democratic elections and their coincidence with the so-called «destape», the process of media-state construction of a pornographic culture open in the public space. In spite of the attempts to link pornography and freedom in the celebratory discourse of the transition, a detailed analysis invites us to describe that moment in terms of a double cession of sovereignty, politics and eroticism. In their encounter, a disturbing imaginary device emerges: the porn-urna, a machine designed for the deferred satisfaction of community re-foundation desires. Through the analysis of a series of passages, fundamentally in films and documentaries of the moment, I argue that, in countercultural spheres, this discourse was analysed in these critical terms, in order to be interrupted by a series of bio-literary practices that demanded the transformation of representation (political and erotic) into presence.